Musical Elements in Yahia Alsamawyâs Divan, INSCRIPTIONS on the Trunk of aPalm - Yahya maroof; Behnam Baqeri (دراسات في اللغة العربيّة وآدابها)
Two kinds of music can be identified in any poetic works: internal music and external music. This research investigates both types and their implications and effects in Yahia Alsamawayâs divan, Inscriptions on the Trunk of a Palm. Concerning external music, the article tries to examine features such as the metric and rhyme patterns. Concerning internal musical elements, the article pays attention to repetitions, the effect of music on meaning, coherence, and some other musical effects such as pun and contrast. It becomes clear that, in this rhythmic ode, the poet has tried to make careful use of small details in internal and external musical resources, in order to enrich his work, and thus express his feelings of pain and sorrow as a result of wounds inflicted upon Iraq.